Vocabulary Acquisition (Incidental) through Watching Subtitled Video Material - Rosales, Alvin Salazar (ELT Forum: Journal of English Language Teaching, 2019)
Subtitle refers to the time-synchronized text on a video that translates the spoken audio to another language. This research deals with the effect of watching subtitled video material on the vocabulary acquisition (incidental) of the Filipino learners of English with an emphasis on the receptive and productive vocabulary knowledge. The study was participated by 100 university students in a private higher education institution in the Philippines. The study used a pretest and posttest design in which the Vocabulary Knowledge Scale developed by Paribakht and Wesche (1993) was employed. The results show that there is a significant difference between the pretest and the posttest performance in vocabulary acquisition in terms of receptive and productive vocabulary knowledge of the participants. The findings imply the integration of subtitled video material in the teaching of vocabulary in Philippine classrooms because of its effectiveness which, up to this point, is not yet realized.